Client’s Satisfaction of a Sti Clinic in the Tertiary Care Centre of Chittagong - Huq, Mohammad Ershadul; Quadir, SM Mahbubul; Ameen, Md Ariful; Sharif , Mohammed (Journal of Chittagong Medical College Teachers’ Association, 2013)
Patient satisfaction with care is a construct reflecting the overall experience of an individual receiving examination and treatment in a given environment during a specified time period. Sexually Transmitted Infections (STI) still accounts for one of the most sensitive health problems in Bangladesh. A cornerstone of effective STI patient management is patient's satisfaction because the physician's diagnosis and prescribed therapies alone are not enough for the recovery of the patient. The aim of this study is to assess the satisfaction level of STI care services rendered by the STI clinic in the tertiary care centre of Chittagong. This cross sectional study was conducted on the patient attending at Outpatient Department (Skin & VD) of Chittagong Medical College Hospital. A total of 112 patients were interviewed by using structured questionnaire. Mean age of the respondent was 34.5+11.6 years. Majority of the respondents belonged to the age group of 25 to 35. Out of the 112 respondent 84 (75%) were male and 28 (25%) were female. Among them 78.6% respondent were Muslim and 21.4% were non Muslim. It was also observed that 17.9% were illiterate and 82.1% were literate. The study focused that education, occupation, marital status, family income, doctor's behavior, staffs behavior; OPD facilities etc. influenced the satisfaction of the respondents. Most of the respondents were satisfied with the behavior of the doctor. They were also satisfied with the service of the doctor. But most of the respondents were dissatisfied with service of the staff. It was also found that educated group of respondents showed more dissatisfaction about the overall service. In contrast those who had less educational qualification were quite satisfied about the service. Most of the respondents commented that doctors behavior were good enough while staffs behavior were not satisfactory. About the overall service of the Outpatient Department, around 41% respondents stated that they were somehow satisfied. The results of the study indicate that the overall satisfaction of the patients mainly depend on the education, occupation and family income of the respondents. JCMCTA 2013 ; 24 (1): 28-34